JEALOUSY, BY ITSELF, DOES NOT CONSTITUTE A BASE MOTIVE (CIPEEX, 2025)
This study examines whether jealousy, taken in isolation, amounts to a base motive for qualifying circumstances and aggravating factors under Brazilian criminal law. It is a doctrinal and case-law study that reviews scholarship and judicial decisions to set objective criteria for identifying base motive and its effects on sentencing. The aim is to distinguish, in practical terms, when jealousy is a mere passion-driven impetus—devoid of ignominy—and when, combined with elements such as contempt for the victim’s dignity, abject purpose, humiliation, or gain, it may qualify the offense. The method comprised a survey of doctrinal sources and appellate rulings, analyzing the offender’s subjective elements, the factual context, and the proportionality between motive and conduct. The findings indicate that jealousy, absent additional circumstances revealing vileness, cruelty, or inhumanity, does not meet the level of blameworthiness required to recognize a base motive; robust evidence is required to establish the link between the vile motive and the crime. It concludes that the base-motive qualifier must be applied restrictively and with reasoned justification, preserving typological coherence and avoiding undue sentence aggravation; judges should make explicit the factual-legal criteria employed and reject base motive when jealousy functions only as an emotional trigger.
Keywords: base motive; jealousy; homicide qualifying circumstance; sentencing